Afaul and afaal in the luma and shuruh - Osama Qawam, Yathrib; Hamid Dahash, Diaa (Al-Adab Journal, 2021)
The deeds and actions of two groups of many buildings came to signify the few rather than the many, and they are the most important and prominent among the buildings of the oligarchs. They represent the basis of the foundations of the collection. They do not differ in importance between them in terms of the abundance of buildings that represent the single material that is gathered on them, and they received the attention of Ibn Jinni in shining And the explanation in their books, which dealt with the book of luminosity, a study and an explanation, and opinions differed in some of the buildings that came to these two groups, so there was no analogy for some of them and they were not analogous to some of the others, and the buildings that were gathered on the building came (do) five buildings (action) verb, verb, verb, and verb) all are auditory except for a verb and other constructs (subject, active, subject and verb) combine its feminine with a verb by analogy, and opinions differed regarding mentioning some of the constructs between the shining and its explanations at times, and the commentaries at times. Abiyas (verb, verb, verb, verb, verb, verb, verb, and verb) are all standard except for (verb), which is a matter of dispute between Ibn Jinni and al-Sharhah. He considered it a few and came as a warning on the original left by the Arabs, the Wasti who considered this plural to be anomalous, and the Kufic, as he went to the action of his analogy, and compiled actions similar to all the movements from the three buildings, and many opinions were shed light on these two structures.